2008
DOI: 10.1016/j.jue.2007.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Which school attributes matter? The influence of school district performance and demographic composition on property values

Abstract: Increasing levels of segregation in American schools raises the question: do home buyers pay for test scores or demographic composition? This paper uses Connecticut panel data spanning eleven years from 1994 to 2004 to ascertain the relationship between property values and explanatory variables that include school district performance and demographic attributes, such as racial and ethnic composition of the student body. Town and census tract fixed effects are included to control for neighborhood unobservables.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(143 citation statements)
references
References 34 publications
4
134
3
2
Order By: Relevance
“…Sedgley, Williams, and Derrick (2008) presented consistent and strong evidence of the capitalization of test scores and demonstrated that properties within good school attendance zones were more expensive than those not situated in these areas. Using panel data of housing transactions in the state of Connecticut spanning eleven years, Clapp, Nanda, and Ross (2008) ascertained the relationship between property values and school attendance zone attributes and supported Black (1999)'s argument that failing to control for unobservable components of neighborhood quality would result in an overestimation of the test score's effect on residential property values.…”
Section: School and Housing Prices In The Western Contextmentioning
confidence: 89%
See 1 more Smart Citation
“…Sedgley, Williams, and Derrick (2008) presented consistent and strong evidence of the capitalization of test scores and demonstrated that properties within good school attendance zones were more expensive than those not situated in these areas. Using panel data of housing transactions in the state of Connecticut spanning eleven years, Clapp, Nanda, and Ross (2008) ascertained the relationship between property values and school attendance zone attributes and supported Black (1999)'s argument that failing to control for unobservable components of neighborhood quality would result in an overestimation of the test score's effect on residential property values.…”
Section: School and Housing Prices In The Western Contextmentioning
confidence: 89%
“…The externality of prestigious schools has been found to be capitalized in housing prices (Black, 1999;Clapp, Nanda, & Ross, 2008).…”
Section: School and Housing Prices In The Western Contextmentioning
confidence: 99%
“…However, the repeat sales index yields quite similar estimates. 16 When a previous sale is not observed, we use the county assessment and adjust that value by the average ratio of sales price to assessed value for that county and quarter, see Clapp, Nanda and Ross (2008). In California, our refinance sample is restricted to mortgages where a previous purchase is observed because property assessments are uninformative as to the value of the underlying property.…”
Section: Delinquencies and Foreclosures By Racementioning
confidence: 99%
“…The overall concept of capitalisation could be summarised that every attribute/characteristic of the market can be capitalised (Oates, 1969(Oates, , 1973Pollakowski, 1973;Abelson and Markandya, 1985;Reback, 2005;Clapp et al, 2008;Stadelmann, 2010).…”
Section: Literature Review the Housing Market Attributesmentioning
confidence: 99%
“…There is a big number of very good and interesting researches studying the provision of adequate education in a school level (primary or high school level) to the residents of a housing market as well as the quality of this provision that influences the housing location choices, and therefore, the housing consumption patterns (Clapp et al, 2008;Reback, 2005;Bayer et al, 2007;Cheshire and Sheppard, 2004;Black, S.E., 1999;Gibbons et al, 2013).…”
Section: The Role Of Higher Educationmentioning
confidence: 99%